A relação teoria e prática na formação do pedagogo à luz do materialismo histórico-dialético - Santos, Manoel Gonçalves dos (2014)
The quality of teacher education is currently too questioned and discussed by researchers from Brazil and the world, in view of the importance that is attributed to education in this social scenario characterized by the expansion of globalization and the globalization of capital. In this discussion about the teacher qualification, the theme of the relationship between theory and practice has gained relevance, considering the formative potential of this binomial is coated, as well as by the dichotomous perspective with which the same has historically been conducted in curriculum settings and training practices. Taking this scenario as motivation, the investigation stems from the following question: What are the implications of the curricular and pedagogical organization of the course in pedagogy of UEFS in the process of appropriation of the relation theory and practice realized by the students of this course? While theoretical and epistemological orientation, this research is based on principles of historical- dialectic materialism. It is a qualitative research, whose lócus is the course of pedagogy of the Universidade Estadual de Feira de Santana/Bahia, and the subjects are 47 students attending the seventh or the eighth semester. The data derive from the application of a questionnaire and documentary analysis of pedagogical political project of course. The theoretical-conceptual framework includes a historical foray that explains the process of structuring the concepts of theory and practice in the history of knowledge, and some eployment of relations arising from these concepts in the configuration and interpretation of reality. Also includes a historical and critical- political analysis of the influence of the interests of the dominant social classes, based in the dominion and expansion of capital, of the Brazilian State, and how these interests have been reverberating in teacher education. Seeking to problematize the reality of our empirical field regarding the theme on screen, as well as trying to demarcate formative principles aligned to theoretical ballast that guides the research, were used as interlocutors, among others, the following authors: Adolfo Sanchez Vasquez, Dermeval Saviani, Luis Carlos de Freitas, Leda Sheibe, Selma Garrido Pimenta and Iria Brzezinski. The results allow to infer that the implications in question have an impact on the training politic and on the technical training of future teachers, understood as complementary dimensions. In the first dimension, taking as a higher ideal of training overcome capitalist mode of production, it was noted that the proposal of the course a countersignature emancipatory direction, but does not define explicitly which joins training history project, if one legitimating of the dictates of capital, or its opposite. It is understandable that such vagueness can be competing for its students to share, as the data show, a vision of the social function of school entered in the capital's landmarks, as well as a concept of relationship between theory and practice circumscribed preponderantly on training model constituted consisting of technical rationality and practical rationality, both hallmarks of teaching practice which does not enhance the ideological and political nuance of education, although noticed signs of a building movement of a vision based on the epistemology of praxis. Regarding the repercussions on the technical dimension, while meeting process to know how to do, the findings indicate a positive perception from the students about the knowledge studied for the expansion of their vision about the reality of the craft in which they will operate. However, their voices reveal, primarily, the existence of a dichotomy of the bargain theory and practice on the course, pointing to problems related to pedagogical work and teaching, and indicating the need for the course thinking, institutionalize and operationalize a collective and interdisciplinary work in such a way, enforcing what assumes its pedagogical political project, to promote effective appropriation of the relationship between theory and practice by students and therefore a better political and technical instrumentalization of these future professionals of basic education.